Planning benefits realization in a collaborative university-industry R&D funded program - Fernandes, Aldora Gabriela Gomes (2018)
This paper presents a benefits management (BM) approach adopted during the planning of a collaborative university-industry R&D funded program, named IC-HMI Program, in order to pursue benefits realization. The BM approach embraced four main phases: 'Identify expected benefits' 'Plan benefits realization' 'Pursue benefits realization' and 'Transfer and ensure benefits realization' each one comprising key activities that should be performed with a clear set of outputs to be generated. Particular focus is given to the benefits identification, and to the development of a Benefit Breakdown Structure (BBS), assuming the key role of such a formatting technique to target project benefits. It is the first and critical step in the BM process. Based on a review of literature, and the three research methods adopted during the IC-HMI case study analysis: a set of 33 benefits were identified, which can be used by professionals and academics as a checklist for benefits identification of their own initiatives. Additionally, the BBS implemented in IC-HMI program to qualify and better understand each benefit and its intrinsic properties, can be used to facilitate planning and benefits realization.